The Impact of Social Media Content on Enrollment Decisions for Bachelor’s Level Education Programs in Nepal Educational Institutions - Adhikari, Sujita; Min, Li; Adhikari, Basanta Prasad (NPRC Journal of Multidisciplinary Research, 2025)
Social media marketing (SMM) has emerged as a crucial recruitment tool for private educational institutions in Nepal, marking a significant shift away from traditional methods such as word-of-mouth and print media. This study investigates the complex impact of SMM on private bachelor’s degree enrollments in the Nepali context, seeking to identify the most effective content strategies and influencing factors, including engagement, credibility, and brand image.The methodology employed a rigorous scoping review, adhering to the Arksey and O’Malley framework and PRISMA-ScR guidelines, to systematically analyze existing evidence. The review clustered thirty-two included studies to synthesize findings regarding student perceptions, marketing strategies, and enrollment outcomes.The synthesis confirms that SMM exerts a significant and positive influence on prospective students’ enrollment decisions. The most critical mechanism of influence is credibility, with students highly prioritizing authentic, peer-driven content (eWOM) and information providing practical utility—such as fees, deadlines, and testimonials—over purely promotional broadcasts. Structural analysis further identified five core online marketing factors—Convenience, Relationship, Outreach, Easy Access, and Value Creation—as significantly influencing enrollment, with Convenience being the strongest predictor. Interestingly, results also indicate a positive correlation between media content accessibility features and enrollment, but a negative correlation with frequent, high-volume user engagement activity.The review highlights a significant strategic gap, noting that institutions often fail to utilize newer platforms, such as Instagram and TikTok, effectively. Methodologically, the field is dominated by correlational quantitative surveys, lacking the causal and contextual depth that mixed-methods designs would provide. This study provides actionable insights for top-level administrators, advocating a shift toward authentic, utility-based, and trust-driven content to optimize digital marketing efforts and enhance enrollment rates.